Long-Term, CD4+ Memory T Cell Response to SARS-CoV-2 - Wirsching, Sebastian; Harder, Laura; Heymanns, Markus; Gröndahl, Britta; Hilbert, Katja; Kowalzik, Frank; Meyer, Claudius; Gehring, Stephan (Frontiers in Immunology, 2022)
The first cases of coronavirus disease-19 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) were reported by Chinese authorities at the end of 2019. The disease spread quickly and was declared a global pandemic shortly thereafter. To respond effectively to infection and prevent viral spread, it is important to delineate the factors that affect protective immunity. Herein, a cohort of convalescent healthcare workers was recruited and their immune responses were studied over a period of 3 to 9 months following the onset of symptoms. A cross-reactive T cell response to SARS-CoV-2 and endemic coronaviruses, i.e., OC43 and NL63, was demonstrated in the infected, convalescent cohort, as well as a cohort composed of unexposed individuals. The convalescent cohort, however, displayed an increased number of SARS-CoV-2-specific T cells relative to the unexposed group. Moreover, unlike humoral immunity and quickly decreasing antibody titers, T cell immunity in convalescent individuals was maintained and stable throughout the study period.